Competitive dialogue in Portugal and Spain - Telles, Pedro (2011)
The competitive dialogue procedure is a new public procurement award procedure first introduced by the Directive 2004118 for the tender of particularly complex contracts, when contracting authorities consider that the use of the open or restricted procedures do not allow for the contract to be tendered. It is not intended to be adopted freely as the open or restricted procedures, but contracting authorities may use it only when the need arises and specific grounds for its use are fulfilled. The procedure was introduced with the stated objective of increasing the flexibility of procurement, which had been already identified as a shortcoming of previous existing EU procurement framework. This thesis studies how the competitive dialogue has been implemented in Portugal and Spain. It covers both the legal transposition and aspects of its practice in these countries., through the use of empirical research methods. Through his research, the author has found that the procedure was implemented very differently in Portugal and Spain with consequences on its use. This study has tried to highlight similarities and differences in the transposition, illustrate how the competitive dialogue is being used in Spain and explain why it is being used only sparingly in Portugal.